Numerical Solutions of the System of Singular Integro-Differential Equations in Classical Hölder Spaces (Advances in Applied Mathematics and Mechanics, 2021)
New numerical methods based on collocation methods with the mechanical quadrature rules are proposed to solvesome systems of singular integro-differential equations that are defined on arbitrary smooth closed contours of the complex plane. We carry out the convergence analysis in classical Hölder spaces. A numerical example is also presented.